# calculus

posted by .

i need to find the derivative using chain rule:
(x^2 + 2x - 6)^2 (1-x^3)^2

i got the answer from a site but the problem is i cannot get my work to match up with the answer, i don't know what im doing wrong.

answer: 10x^9 + 36x^8 − 64x^7 − 182x^6 + 168x^5 + 80x^4 + 196x^3 − 204x^2 − 16x−24

my work:
f'(x) = [2(x^2 + 2x - 6)*(2x + 2)]*(1-x^3)^2 + [2(1-x^3)*(3x^2)]*(x^2 +2x-6)^2

f'(x)=2(2x^3 +6x^2 -8x-12)*(1-x^3)^2 +[2(3x^2 -3x^5)]*(x^2 +2x-6)(x^2 +2x-6)

f'(x)= (4x^3 +12x^2 -16x-24)*(1-2x^3 +x^6) +(6x^2 -6x^5)*(x^4 +4x^3 -8x^2 -24x+36)
f'(x)=4x^9 +12x^8 -16x^7 -32x^6 -24x^5 +32x^4 +52x^3 +12x^2 -16x-24)+(-6x^9 -24x^8 +48x^7 -138x^6 -198x^5 -48x^4 -144x^3 +216x^2)

f'(x)=-2x^9 -12x^8 +32x^7 -170x^6 +222x^5 -16x^4 -92x^3 +228x^2 -16x -24

its 1am and i could have made some arithmetic errors but im fairly certain there accurate for the most part

• calculus -

well, maybe they're as accurate as your spelling...

Your very first line is in error: should be -3x^2 toward the end.

Fix that, and everything's ok.

If you visit wolframalpha.com and enter

derivative (x^2 + 2x - 6)^2 (1-x^3)^2

you will get several different ways of writing it.

If you enter

[2(x^2 + 2x - 6)*(2x + 2)]*(1-x^3)^2 + [2(1-x^3)*(-3x^2)]*(x^2 +2x-6)^2

you will get the same answer.

Devil's in the details, as usual. Unless otherwise instructed, I'd probably not take it all the way to a single expanded expression.

• calculus -

Y=2x^3-16x^2+64x+1

## Similar Questions

1. ### calculus

Find the derivative using the chain rule. f(x) = ((3x-7)/(6x+3))^4 f '(x) = let u= 3x-7 v= (6x+3)^-4 Then d(uv)= u dv + v du du= 3 dv= -4(6x+3)^-5 (6) so what's f'(x)?
2. ### Calculus (Help)

Also I would like to know how to set this problem up in finding the answer: Find the second derivative. y= sqrt(3x+4) Thanks, P.S. I tried taking 3x+4 and squaring it to the 1/2. I thought that might've been the same, then I took the …
3. ### MoRe HeLp PlEaSe!! (calc)

Also can I get some help with this LONG, TIRESOME PROBLEM?
4. ### Math, Calculus

Find the derivative of the function. y= xcosx - sinx What's the derivative?
5. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
6. ### Calculus

I finished this problem but I wanted some feedback because I don't know if it's entirely correct. Suppose that functions f and g and their derivatives with respect to x have the following values at x=2. f(x)=8 g(x)=2 f'(x)=1/3 g'(x)=-3 …
7. ### calculus

V(h) = pie/3(R^2h-h^3) take the derivative with respect to h. using the chain rule I got: V'(h) = pie/3(2Rh+R^2-3h^2) but this is not the correct answer. what did I do wrong?
8. ### Calculus

Find the derivative of y with respect to x: y=(1+cos²x)^6 y'=6(1+cos²x)^5 How do you derive inside the brackets?
9. ### calculus

Please help. Applying the chain rule, how do I find the derivative of f(x)=In(e^x-e^-x) (x>0) and then using this answer use the quotient rule to find the second derivative. I cannot do this so any answer greatly appreciated.
10. ### calculus

i need to find the derivative using chain rule and show steps: y= (x) / ((x^2)-1)^(-1/2) and is it possible to have free tutoring online like through a chatroom?

More Similar Questions